Shape evolution of the interest rate term structure - Biwei Chen (Review of Economic Analysis (REA), 2021)
This paper adopts a novel approach to studying the evolution of interest rate term structure over the U.S. business cycles and to predicting recessions. Applying an effective algorithm, I classify the Treasury yield curve into distinct shapes and find the less frequent shapes intrinsically linked to the recessions in the post-WWII data. In forecasting recessions, the median-short yield spread trumps the long-short spread for horizons up to 17 months ahead and the yield curve shape is nearly impressive as the median-short spread. Overall, the yield curve shape is an informative but more succinct indicator than the spreads in studying the term structure. Key words: Business cycle, recession forecast, U.S. Treasury yield curve, yield spreads.
Keywords: E32; E43; E47; G12; C52; C53; C82; 330; Business cycle; recession forecast; U.S. Treasury yield curve; yield spreads